Use of Ventilation-Perfusion Single-Photon Emission Computed Tomography to Select the Target Lobe for Endobronchial Valve Lung Volume Reduction - Tee, Vanessa Sze Theen; Nguyen, Phan; Jersmann, Hubertus; Grosser, Dion; Crouch, Benjamin; Lorraine, Brett; Chew, Chong Ghee (Respiration, 2021)
Background: Quantitative planar ventilation-perfusion (VQ) has a complementary role in target lobe selection for endobronchial valve lung volume reduction (EBV-LVR), especially in homogenous disease. We investigated a novel method of lung lobar quantitation using VQ single-photon emission computed tomography (SPECT) with computed tomography (CT) to generate a parameter called the ventilation-perfusion differential index (VQDI). Aim: The aim of this study was to validate VQDI as a parameter for target lobe selection in EBV-LVR against the gold standard test of quantitative computed tomography (qCT). Methods: This study was a prospective, multi-centre, single-blinded, observational study of EBV-LVR patients. Baseline and 3-month post intervention VQ SPECT and qCT were performed. The target lobe was chosen using qCT and planar VQ report (CT TL ) whilst blinded to VQDI. Post EBV-LVR, our nuclear physician, blinded to CT TL , selected a target lobe using deidentified VQDI (VQDI TL ). Inter-rater agreement between CT TL and VQDI TL was calculated by Kappa statistic. Treatment outcomes were analysed with a linear mixed-effects model. Results: There was a high concordance between CT TL and VQDI TL in 16 patients (89%, Kappa statistic = 0.85). Post EBV-LVR, our subjects showed significant changes in FEV1 (mean difference [MD] +150 mL, p < 0.001), target lobe volume reduction (MD −973 mL, p < 0.001), residual volume (MD −800 mL, p < 0.001), and St. George’s Respiratory Questionnaire score (MD −11, p = 0.001). Improvements in 6-minute walk distances did not reach statistical significance. Conclusion: In this study of treatment responders, EBV-LVR target lobe selection using VQDI concurs with qCT and thus supports its value for this purpose. It complements qCT and may potentially be of synergistic value especially in homogenous emphysema.